Parent-Offspring Relationships Following Mass Spawning of Wild Adriatic Sea Bass (Dicentrarchus labrax) - Jelena Lončar; Renata Barić; Lav Bavčević; Branko Kozulić (Food Technology and Biotechnology, 2014)
We have genotyped 44 fishes caught in the wild (Novigrad Sea, Croatia) using 11 microsatellite tetranucleotide markers. They were divided in two groups and after natural mass spawning, we selected 500 offspring for genotyping following their labelling with electronic tags. All fish in the parental group could be identified based on unique genotypes, and a significant number of private alleles, the alleles found only in one fish, greatly facilitated subsequent parent-offspring assignments. The majority of potential parents left no progeny, while just six of them generated over 70 %. Such highly skewed reproduction success, observed also in other studies, can quickly lead to a highly inbred population in just a few selection cycles. This kind of genetic analysis is helpful for planning of future selective breeding, where faster progress will be made possible based on the soon to be completed sea bass genome sequence.